SISTEM INFORMASI PENDAFTARAN PASIEN PELAYANAN KEDOKTERAN KEPOLISIAN (DOKPOL) PADA RUMAH SAKIT BHAYANGKARA JAMBI : System;Information;Patient Registration;Hospital;Web-Based;Codeignete - Djauhari, Teuku; Huda Aminuddin, Fattachul; Bahri, Faisal (LP2M Universitas Nurdin Hamzah, 2021)
Bhayangkara Hospital Jambi City is one of the hospitals that will be the best hospital in Jambi City. With the Bhayangkara Hospital in Jambi City, it is expected to help the community, especially in health services. The purpose of this study is to create a web-based Dokpol information system so that registration errors do not occur or loss occurs. Registration is registering/filling in biodata for registration as a patient. To manage this information, we need a system that will assist the process of making registration data reports. The research was conducted using a qualitative approach, namely a research approach that is descriptive in nature and tends to use analysis. Process and meaning are highlighted in qualitative research. Design and Build a web-based Registration Information System is made using the programming language php 5.1 and MYSQL 4.8.4 database. The results of this study are to design a web-based Dokpol information system that is expected to help inform patient registration, check results with the system, generate patient reports and produce examination reports, can facilitate the decision-making process, be able to provide information about patient data, doctor data. , as well as reports appropriately with the availability of timely, accurate, and relevant information that can assist staff and officers in carrying out registration activities and is expected to improve the performance of employees.